Association between exposure to bisphenols and per- and polyfluoroalkyl substances and behavioral problems among Chinese preschoolers - Ruo-yu Li; Jun Wu; Wan Xiao; Yang Zhou; Ke Liang; Jia-ying Bao; Zhi-yuan Yao; Chao Zhang; Yu-hui Wan (Ecotoxicology and Environmental Safety)
In order to fill the gap in previous research, we aim to investigate the relationship between single and co-exposure to bisphenols (BPs) and per- and polyfluoroalkyl substances (PFAS) and behavioral problems among Chinese preschoolers. The current study measured urinary BPs and PFAS concentrations in 823 Chinese preschoolers. The children’s behavioral problems were assessed using the Conners’ Parent Symptom Questionnaire (PSQ). Binary logistic regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) were used to examine the association between single or co-exposure to all chemicals and behavioral problems among preschoolers. After controlling for covariates, binary logistic regression results showed that bisphenol AP (BPAP), bisphenol B (BPB), bisphenol S (BPS), perfluorobutanesulfonic acid (PFBS), perfluorohexanesulfonic acid (PFHxS), and perfluorooctane sulphonate (PFOS) were significantly associated with children’s behavioral problems (OR = 1.89–2.60, 95 % CI: 1.01–5.21). The WQS index was significantly positively associated with behavioral problems (OR = 2.01, 95 % CI: 1.24–3.32). BPAP and PFHxS were the chemicals with the most significant weights. BKMR results also found that the mixture of BPs and PFAS had a partially significant positive association with preschoolers’ behavioral problems. This study indicated that a mixture of urinary BPs and PFAS has a combined effect on behavioral problems in preschoolers. In addition, BPAP and PFHxS, which are common substitutes for BPA and PFOS respectively, have a greater impact on preschoolers’ behavioral problems and are worthy of further attention.